Pentingnya Kosakata dan Tata Bahasa untuk Mengukur Keterbacaan dan Tingkat Bahasa - Chrysovalantou Kapeta (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2024)
The purpose of this research is to determine the level of difficulty (Readability) and the language level of texts written by non-Italian speakers. For this purpose, texts produced by Greek candidates (B1 and B2 level) according to the Greek State Certificate Exam (KPG) for the Italian language were selected. All data was collected from the KPG exams of May 2015 and November 2016. Specifically, from 1000 randomized KPG notebooks, a total of 80 notebooks were used, (B1 and B2) that were first digitized in manual form. In the second and third phase, these texts were measured using the READ-IT and SPSS.24 tool. The results lead to the fact that both the correct use of vocabulary, i.e., spelling and the appropriate vocabulary in relation to the content of the text, determine the language level and degree of difficulty of produced texts. All results are part of an existing tool named trat.exe used by the University EKPA and Aristotle to measure the Readability regarding the exams of Italian language of KPG. Of utmost importance would be the future deepening of the parameters of writing with the goal of developing even more advanced software.